The 9th Judgment - Patterson, James 1947-; Paetro, Maxine (New York : Little, Brown, 2010)
After an assailant guns down a mother and her infant at a mall and a cat burglar kills the wife of an A-list actor, Lindsay Boxer and her partner Rich must pick up the pieces, but not before one of the killers forces Lindsay to put her life on the line.
Keywords: Women detectives -- Fiction -- San Francisco (Calif.); Homicide -- Fiction; Criminal investigation -- Fiction; Female friendship -- Fiction; Large print books; San Francisco (Calif.) -- Fiction; Fiction